True lies [videorecording (DVD)] - Cameron, James, 1954-; Schwarzenegger, Arnold; Curtis, Jamie Lee, 1958-; Arnold, Tom, 1959-; Paxton, Bill; Carrere, Tia; Malik, Art; Heston, Charlton (20th Century Fox Home Entertainment, 1999)
Harry Tasker is a top spy for the ultra-secret Omega Sector, but his wife thinks he's just a boring computer salesman. Then his two lives collide when he and his wife find themselves kidnapped by international terrorists.